Andrea Pozzo and the Jesuit "Theatres" of the Seventeenth Century - Horn, Andrew (Journal of Jesuit studies, 2019)
Considered within the context of Jesuit theatre and liturgy, and within the broader culture of spectacle and ritual in the era of Counter-Reform, the works of art and architecture commissioned by the Jesuits in the seventeenth century can be read as "theatres" of religious performance. This concept is given an ideal case study in the work of Jesuit artist Andrea Pozzo (1642-1709). In this essay I present Pozzo's work within the context of ritual and prayer for which it was produced, focusing on two of his religious scenographies and two of his lesser-known painting projects. As I consider their use of allegory, emblems and symbols, visual narratives, spatial illusions, and architecture, I argue that both the scenographies and the permanent church decorations achieve persuasion through the engagement of the observer as a performer in a ritual involving both internal and external performance.